The Impact of Liquidity Moderation: Studies on Transportation Subsector Service Companies Listed on the IDX for the 2012-2020 period - Akhmadi Akhmadi (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2023)
The purpose of this research was to analyze the influence of capital structure on Profitability with Liquidity as a moderating variable. The population of this research is transportation sub-sector companies listed on the Indonesia Stock Exchange for the period 2012-2018. The research method in this study is a causal-comparative. Hypothesis testing using moderate regression. Based on the sampling technique purposive sampling researcher used 25 with amounts of 175 data. The results of this study show that the Capital Structure has a significant effect on profitability while on Liquidity, as moderation variables have no significant effect on the relationship of capital structure to profitability, which means Liquidity weakens in moderating the relationship of capital structure to Profitability.